MONYET EKOR PANJANG (Macaca fascicularis) SEBAGAI HEWAN MODEL DAN ETIKA PENGGUNAANNYA - Ratni Ernita; Tatang Mitra Setia; Fitriya Nur Annisa Dewi; Huda Shalahudin Darusman (UIN Sunan Gunung Djati Bandung, 2021)
The use of nonhuman primates as animal models in biomedical research has an important role in the development of human health. A close phylogenetic relationship with humans as well as similarities in genetics, behavior and biochemical activities are some of the things that underlie the selection of nonhuman primates as animal models. Cynomolgus macaques (Macaca fascicularis) is one of Indonesia's endemic primates which is widely used in research. Its current status as Appendix II in Convention International Trade in Endangered Species of Wild Fauna and Flora (CITES) defines that the population remains quite large in nature, which allows this species to be used in research, as long as they are sourced from the captive-bred population. Although the use of nonhuman primates in research is unavoidable, it is warranted that potential harm such as distress, discomfort, stress, pain and even death have to be avoided or minimized. Implementation of ethics is therefore required for the care and use of cynomolgus macaques in research, such as by assuring that the 3R principles (replacement, reduction, refinement) are met. Refinement can be achieved by applying the principles of animal welfare known as the Five Freedoms of Animal Welfare (5F). The active implementation of these ethical principles continues to develop along with the development of science and technology, and receives more spotlight in the world of biomedical research globally. Ensuring adequate implementation of ethical principles in research with nonhuman primates in each research institution must be under the oversight of an IACUC (Institutional Animal Care and Use Committee), which will weigh on the harm to animals compared to the benefits to humans. Active implementation of the principles of ethics and animal welfare will result in increasing the quality of research, serves as an assurance to the society, and in compliance to the requirements for good scientific publication.